ANTIDIABETIC -GLYCOSIDASE ANTIDIABETIC ENZYME INVOLVING ACTIVITY TEST FROM BUTANOL FRACTION OF AREUY KIKUNTI LEAVES IN VITRO (Pothos Junghunii De Vreise) - Willy Pratama Wijaya; Purwati Purwati (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2022)
Diabetes mellitus is a disease with high blood glucose levels due to body’s lack of hormone insulin. Examples of natural ingredients that can be used asa antidiabetic are several plants from the genus pothos. This study use the leaves of Aurey kikunti (Pothos junghuhnii de Vreise). The purpose of this study was to deteminate the inhibitory activity of the anti-diabetic α-glikosidase enzyme from the Carinol fraction of Areuy kikunti leaves. The test carried out were the inhibitor activity of the α-glucosidase enzyme with acarbose as a comparison. Antidiabetic activity tets using microplet and analyzed with Elisa reade. In the inhibitor activity (%inhibition) with a concentration of 1000ppm, the butanol fraction yield a value of 8,155%,  while the inhibitory activity (%inhibition) of acarbose was 98,349%. From the results obtained, it shows that it has not been able to inhibit 50% of enzyme activity so that it is included in the week category, when compared to the inhibition value of acarbose. It can be concluded that the butanol fraction has no antidiabetic activity.